A method for preparing a copper-aluminum alloy conductor for a radio frequency coaxial cable of a network base station
By using a discharge plasma sintering furnace to mix modified nano cerium carbide with metal powder for multiple vacuum sintering, continuous annealing, rolling and drawing of copper-aluminum alloy wires, the problems of wire oxidation and intergranular corrosion are solved, and high strength, high conductivity and good oxidation resistance are achieved.
Patent Information
- Application Number
- CN202411298988.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Existing copper-aluminum alloy wires are prone to oxidation and intergranular corrosion problems during long-term use, and it is difficult to achieve high strength and high plasticity at the same time.
A discharge plasma sintering furnace was used to mix modified nano cerium carbide with metal powder for multiple vacuum sintering, and continuously annealing, rolling and drawing to obtain copper-aluminum alloy wire. This method improves the ductility by filling the metal grain boundaries of nano cerium carbide, forming a reinforced phase with Cu-4Al powder and Cu-4Al powder mixed sintering, and then forming a stacked layered structure and a continuous oxide film by repeated firing, thereby improving the oxidation resistance and mechanical properties of the wire.
The high strength, high conductivity and good oxidation resistance of copper-aluminum alloy wires are achieved, while improving the plasticity and toughness of the wires, and maintaining good performance under high load and pressure.
Smart Images

Figure BDA0005047025270000071 
Figure BDA0005047025270000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-aluminum alloy preparation, and in particular to a method for preparing a copper-aluminum alloy conductor for a radio frequency coaxial cable of a network base station. Background Art
[0002] At present, the use of high-frequency signal transmission in wireless communications can reduce signal attenuation, improve its anti-interference ability, and achieve long-distance signal transmission. Copper-aluminum alloy wire combines the high conductivity of copper and the low cost and light weight of aluminum, making it very suitable for use as a transmission cable for high-frequency signals. At the same time, copper-aluminum alloy wire has also been widely used in bus ducts, welding wires and other fields.
[0003] Although copper and aluminum are both metal materials with good corrosion resistance, they may still suffer from oxidation and intergranular corrosion during long-term use. At the same time, the strength and plasticity of metal structural materials are two important indicators for evaluating their mechanical properties, but few materials can achieve high strength and high plasticity at the same time. Therefore, it is particularly important to invent an oxidation-resistant, high-strength, and highly conductive copper-aluminum alloy wire. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a copper-aluminum alloy conductor for a radio frequency coaxial cable of a network base station, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a copper-aluminum alloy conductor for a network base station radio frequency coaxial cable, wherein the aluminum alloy conductor for a network base station radio frequency coaxial cable is obtained by multiple vacuum sintering of modified nano-cerium carbide and metal powder in a spark plasma sintering furnace, continuous annealing, rolling and wire drawing.
[0006] Furthermore, the modified nano-cerium carbide is prepared from metallic cerium, graphite and nano-iron powder.
[0007] Furthermore, the metal powder includes Cu powder, Cu-4Al powder and Al powder.
[0008] Furthermore, a method for preparing a copper-aluminum alloy conductor for a radio frequency coaxial cable of a network base station comprises the following preparation steps:
[0009] (1) 6 to 14 parts of metallic cerium powder, 18 to 42 parts of graphite, 30 to 64 parts of NaCl, and 3 to 7 parts of NaF are mixed uniformly, placed in a vacuum reactor for reaction for 30 to 70 minutes, then soaked in 71 to 93 parts of a dilute acid solution for 1 to 3 hours, rinsed with 84 to 102 parts of water, and dried to obtain nano-cerium carbide;
[0010] (2) 24 to 56 parts of nano-cerium carbide are placed in a smelting crucible, and 13 to 45 parts of nano-iron powder are melted to obtain a molten liquid, and the crucible is placed in a tightly coupled vacuum induction furnace. When the ambient temperature reaches 800° C., the molten liquid is atomized and sprayed to obtain modified nano-cerium carbide;
[0011] (3) 42 to 56 parts of Cu and 13 to 27 parts of modified nano-cerium carbide are uniformly mixed and placed in a spark plasma vacuum sintering furnace, and the temperature is raised to 800 to 1000°C at a certain rate, and an external pressure of 25KN is applied for 10 to 20 minutes, and argon is introduced to quickly cool down, and 19 to 25 parts of Cu-4Al powder and 23 to 31 parts of Cu powder are added, and the temperature is raised to 800 to 1000°C at a certain rate, and an external pressure of 25KN is applied for 10 to 20 minutes, and argon is introduced to quickly cool down, and then 21 to 33 parts of Al powder, 19 to 25 parts of Cu-4Al powder, and 7 to 15 parts of modified nano-cerium carbide are added, and the temperature is raised to 800 to 1000°C at a certain rate, and an external pressure of 25KN is applied for 10 to 20 minutes, and argon is introduced to quickly cool down to obtain a composite alloy block;
[0012] (4) repeating step (3) three times, placing the mixture in a muffle furnace under argon protection for 30 to 50 minutes, and slowly cooling the mixture to 650° C. to obtain a multi-layer composite alloy block;
[0013] (5) placing the multilayer composite alloy block in a horizontal continuous casting machine at a pouring temperature of 650 to 750° C. and a horizontal continuous casting speed of 800 to 1300 mm / min to obtain a round wire rod blank;
[0014] (6) The round wire rod blank is placed in an alloy wire drawing machine at 450-550° C. and drawn into a wire with a diameter of 1.38 mm, thereby obtaining a copper-aluminum alloy wire for a radio frequency coaxial cable of a network base station.
[0015] Furthermore, the temperature of the vacuum reaction furnace in step (1) is 1100-1500° C., the vacuum degree is 0.01 Pa-0.1 Pa, and the dilute acid solution is 0.5-1.5 mol / L sulfuric acid solution.
[0016] Furthermore, the atomization spraying conditions in step (2) are: atomization medium Ar gas, atomization pressure 1.0-5.0 MPa, atomization flow rate 18-30 m 3 / min.
[0017] Furthermore, the particle size of the Cu powder, Cu-4Al powder and Al powder in step (3) is 250-450 mesh.
[0018] Furthermore, the vacuum degree of the spark plasma vacuum sintering furnace in step (3) is 1 to 15 Pa.
[0019] Furthermore, in step (3), the heating rate is 80°C / min, and the rapid cooling rate is 100-160°C / h, cooling to 700°C.
[0020] Furthermore, the insulation temperature in step (4) is 900-1000° C., and the slow cooling rate is 20-40° C. / h.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] The invention utilizes a discharge plasma sintering furnace for vacuum sintering. During the sintering process, the plasma generated by the pulse current and the pressurized sintering are used to rapidly sinter the powder at a relatively low temperature to make it dense. On this basis, Cu powder is mixed with modified nano-cerium carbide for one sintering, and the nano-cerium carbide fills the metal grain boundary, so that the metal can bear more loads. Cu-4Al powder and Cu powder are used as an intermediate layer for a second sintering to form a strengthening phase, which can bear a larger load and pressure and improve the strength and hardness of the alloy. Al powder, Cu-4Al powder and modified nano-cerium carbide are mixed for a third sintering to improve the ductility of the alloy, inhibit the growth of grains in the alloy and improve the toughness of the alloy. The stacked layer structure is formed by repeating the process three times, and the transition interface with double gradient distribution of closely combined elements and stacking fault energy can coordinate multiple deformation mechanisms, relieve stress concentration at the interface and maintain good plasticity. Continuous annealing and slow cooling are then performed to form a continuous and smooth oxide film, so as to improve the anti-oxidation performance. Finally, rolling and wire drawing are performed to obtain the copper-aluminum alloy wire.
[0023] Secondly, modified nano-cerium carbide is made of metallic cerium, graphite and nano-iron powder; the metallic cerium powder is dissolved in a molten salt medium, and the cerium element diffuses to the graphite surface and reacts with it in situ to form a cerium carbide layer, thereby achieving the effects of anti-oxidation and enhanced conductivity; then a tightly coupled vacuum induction furnace is used to atomize the nano-iron powder and combine it with cerium carbide to form a double-layer coating, which is combined with the alloy during firing to enhance conductivity, while absorbing and guiding the magnetic field, reducing interference from the external magnetic field, and achieving the effect of electromagnetic shielding. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the copper-aluminum alloy conductor for the radio frequency coaxial cable of the network base station prepared in the following examples are as follows:
[0026] Tensile strength: the embodiment and comparative example with the same length were tested according to GB / T1176-2013.
[0027] Elongation at break: Take the embodiment and comparative example of the same length and test them with reference to GB / T34505-2017 "Room Temperature Tensile Test Method for Copper and Copper Alloy Materials".
[0028] Electrical conductivity: The embodiment and comparative example with the same length were tested according to GB / T3048.0-2007.
[0029] Oxidation resistance: The same length of the example and the comparative example were measured in a 200°C environment for 1000 hours. The samples were classified into Class C (weight increase> 0.2 mg / cm 2 ), Class B (weight increase at 0.2mg / cm 2 ~0.1mg / cm 2 ) and Grade A (weight gain <0.1 mg / cm 2 ).
[0030] Example 1
[0031] (1) 6 parts of metal cerium powder, 18 parts of graphite, 30 parts of NaCl and 3 parts of NaF were mixed evenly, reacted in a vacuum reactor at 1100° C. and a vacuum degree of 0.01 Pa for 30 minutes, then soaked in 71 parts of a 0.5 mol / L dilute acid solution for 1 to 3 hours, rinsed with 84 to 102 parts of water, and dried to obtain nano-cerium carbide;
[0032] (2) 24 to 56 parts of nano-cerium carbide are placed in a melting crucible, and 13 parts of nano-iron powder are melted to obtain a molten liquid. The crucible is placed in a tightly coupled vacuum induction furnace. When the ambient temperature reaches 800°C, an atomizing medium of Ar gas is used, the atomizing pressure is 1.0 MPa, and the atomizing flow rate is 18 m 3 / min atomizing and spraying the melt to obtain modified nano-cerium carbide;
[0033] (3) 42 parts of 250-mesh Cu and 13 parts of modified nano-cerium carbide were mixed and placed in a spark plasma vacuum sintering furnace, and the temperature was raised to 800°C at 80°C / min, and an external pressure of 25 KN and a vacuum degree of 1 Pa were applied for 10 min. Argon was introduced and the temperature was rapidly lowered to 700°C at 100°C / h. 19 parts of 250-mesh Cu-4Al powder and 23 parts of 250-mesh Cu powder were added, and the temperature was raised to 800°C at 80°C / min. The pressure was 25KN and the vacuum was 1Pa for 10min, and the temperature was rapidly reduced to 700℃ by passing argon at 100℃ / h, and then 21 parts of 250-mesh Al powder, 19 parts of 250-mesh Cu-4Al powder, and 7 parts of modified nano-cerium carbide were added and the temperature was increased to 800℃ at 80℃ / min, and the pressure was 25KN and the vacuum was 1Pa for 10min, and the temperature was rapidly reduced to 700℃ by passing argon at 100℃ / h to obtain a composite alloy block;
[0034] (4) repeating step (3) three times, placing the mixture in a muffle furnace under argon protection at 900° C. for 30 min, and slowly cooling the mixture to 650° C. at a rate of 20° C. / h to obtain a multi-layer composite alloy block;
[0035] (5) placing the multilayer composite alloy block in a horizontal continuous casting machine at a pouring temperature of 650° C. and a horizontal continuous casting speed of 800 mm / min to obtain a round wire rod blank;
[0036] (6) The round wire rod blank is placed in an alloy wire drawing machine and drawn into a wire with a diameter of 1.38 mm at 450° C., thereby obtaining a copper-aluminum alloy wire for a network base station radio frequency coaxial cable.
[0037] Example 2
[0038] (1) 10 parts of metallic cerium powder, 30 parts of graphite, 47 parts of NaCl, and 5 parts of NaF were mixed evenly, reacted in a vacuum reactor at 1300° C. and a vacuum degree of 0.06 Pa for 50 min, then soaked in 82 parts of a 1.0 mol / L dilute acid solution for 2 h, rinsed with 93 parts of water, and dried to obtain nano-cerium carbide;
[0039] (2) 40 parts of nano-cerium carbide were placed in a smelting crucible, and 29 parts of nano-iron powder were melted to obtain a molten liquid. The crucible was placed in a tightly coupled vacuum induction furnace. When the ambient temperature reached 800°C, the atomizing medium was Ar gas, the atomizing pressure was 3.0 MPa, and the atomizing flow rate was 24 m 3 / min atomizing and spraying the melt to obtain modified nano-cerium carbide;
[0040] (3) 49 parts of 350-mesh Cu and 20 parts of modified nano-cerium carbide were mixed and placed in a spark plasma vacuum sintering furnace, and the temperature was raised to 900°C at 80°C / min, and an external pressure of 25KN and a vacuum degree of 8Pa were applied for 15 minutes. Argon was introduced and the temperature was rapidly lowered to 700°C at 130°C / h. 22 parts of 350-mesh Cu-4Al powder and 27 parts of 350-mesh Cu powder were added, and the temperature was raised to 900°C at 80°C / min. Apply a pressure of 25KN and a vacuum degree of 8Pa for 15min, introduce argon and rapidly cool down to 700°C at 130°C / h, then add 27 parts of Al powder, 22 parts of 350-mesh Cu-4Al powder, and 11 parts of modified nano-cerium carbide and heat up to 900°C at 80°C / min, apply a pressure of 25KN and a vacuum degree of 8Pa for 15min, introduce argon and rapidly cool down to 700°C at 130°C / h to obtain a composite alloy block;
[0041] (4) repeating step (3) three times, placing the mixture in a muffle furnace under argon protection at 950° C. for 40 min, and slowly cooling the mixture to 650° C. at a rate of 30° C. / h to obtain a multi-layer composite alloy block;
[0042] (5) casting the multilayer composite alloy block in a horizontal continuous casting machine at a pouring temperature of 700° C. and a horizontal continuous casting speed of 1050 mm / min to obtain a round wire rod blank;
[0043] (6) The round wire rod blank is placed in an alloy wire drawing machine and drawn into a wire with a diameter of 1.38 mm at 500° C., thereby obtaining a copper-aluminum alloy wire for a network base station radio frequency coaxial cable.
[0044] Example 3
[0045] (1) 14 parts of metallic cerium powder, 42 parts of graphite, 64 parts of NaCl, and 7 parts of NaF were mixed uniformly, reacted in a vacuum reactor at 1500° C. and a vacuum degree of 0.1 Pa for 70 min, then soaked in 93 parts of a 1.5 mol / L dilute acid solution for 3 h, rinsed with 102 parts of water, and dried to obtain nano-cerium carbide;
[0046] (2) 56 parts of nano-cerium carbide were placed in a smelting crucible, and 45 parts of nano-iron powder were melted to obtain a molten liquid. The crucible was placed in a tightly coupled vacuum induction furnace. When the ambient temperature reached 800°C, an atomizing medium of Ar gas was used, the atomizing pressure was 5.0 MPa, and the atomizing flow rate was 18-30 m 3 / min atomizing and spraying the melt to obtain modified nano-cerium carbide;
[0047] (3) 56 parts of 450-mesh Cu and 27 parts of modified nano-cerium carbide were mixed and placed in a spark plasma vacuum sintering furnace, and the temperature was raised to 1000°C at 80°C / min, and an external pressure of 25 KN and a vacuum degree of 15 Pa were applied for 20 min. Argon was introduced and the temperature was rapidly lowered to 700°C at 160°C / h. 25 parts of 450-mesh Cu-4Al powder and 31 parts of 2450-mesh Cu powder were added, and the temperature was raised to 1000°C at 80°C / min. The pressure was 25KN and the vacuum was 15Pa for 20min, and the temperature was rapidly reduced to 700°C at 160°C / h by introducing argon gas, and then 33 parts of 450-mesh Al powder, 25 parts of 450-mesh Cu-4Al powder, and 15 parts of modified nano-cerium carbide were added and the temperature was increased to 1000°C at 80°C / min, and the pressure was 25KN and the vacuum was 15Pa for 20min, and the temperature was rapidly reduced to 700°C at 160°C / h by introducing argon gas to obtain a composite alloy block;
[0048] (4) repeating step (3) three times, placing the mixture in a muffle furnace under argon protection at 1000° C. for 50 min, and slowly cooling the mixture to 650° C. at a rate of 40° C. / h to obtain a multi-layer composite alloy block;
[0049] (5) casting the multilayer composite alloy block in a horizontal continuous casting machine at a pouring temperature of 750° C. and a horizontal continuous casting speed of 1300 mm / min to obtain a round wire rod blank;
[0050] (6) The round wire rod blank is placed in an alloy wire drawing machine and drawn into a wire with a diameter of 1.38 mm at 550° C., thereby obtaining a copper-aluminum alloy wire for a radio frequency coaxial cable of a network base station.
[0051] Comparative Example 1
[0052] The difference between Comparative Example 1 and Example 2 is that step (3) is different. Step (3) is changed to: 22 parts of 350-mesh Cu-4Al powder and 27 parts of 350-mesh Cu powder are heated to 900°C at 80°C / min, with an external pressure of 25KN and a vacuum degree of 8Pa for 15min, and argon is introduced to rapidly cool down to 700°C at 130°C / h, and then 27 parts of mesh Al powder, 22 parts of 350-mesh Cu-4Al powder and 11 parts of modified nano-cerium carbide are added to heat to 900°C at 80°C / min, with an external pressure of 25KN and a vacuum degree of 8Pa for 15min, and argon is introduced to rapidly cool down to 700°C at 130°C / h to obtain a composite alloy block. The remaining steps are the same as those in Example 2.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 2 is that step (3) is different. Step (3) is changed to: 49 parts of 350-mesh Cu and 20 parts of modified nano-cerium carbide are placed in a spark plasma vacuum sintering furnace, heated to 900°C at 80°C / min, with an external pressure of 25KN and a vacuum degree of 8Pa for 15min, and then argon is introduced to rapidly cool to 700°C at 130°C / h, followed by adding 27 parts of Al powder, 22 parts of 350-mesh Cu-4Al powder, and 11 parts of modified nano-cerium carbide, heated to 900°C at 80°C / min, with an external pressure of 25KN and a vacuum degree of 8Pa for 15min, and then argon is introduced to rapidly cool to 700°C at 130°C / h to obtain a composite alloy block. The remaining steps are the same as those in Example 2.
[0055] Comparative Example 3
[0056] The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: 49 parts of 350-mesh Cu and 20 parts of modified nano-cerium carbide are placed in a spark plasma vacuum sintering furnace, heated to 900°C at 80°C / min, with an external pressure of 25KN and a vacuum degree of 8Pa for 15min, and argon is introduced to rapidly cool to 700°C at 130°C / h, 22 parts of 350-mesh Cu-4Al powder and 27 parts of 350-mesh Cu powder are added, heated to 900°C at 80°C / min, with an external pressure of 25KN and a vacuum degree of 8Pa for 15min, and argon is introduced to rapidly cool to 700°C at 130°C / h to obtain a composite alloy block. The remaining steps are the same as those in Example 2.
[0057] Comparative Example 4
[0058] The difference between Comparative Example 4 and Example 2 is that step (4) is different, and step (4) is changed to: placing the composite alloy block in a muffle furnace under argon protection at 950° C. for 40 minutes, and slowly cooling to 650° C. at 30° C. / h to obtain a multi-layer composite alloy block. The remaining steps are the same as in Example 2.
[0059] Comparative Example 5
[0060] The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: repeat step (3) three times, place in a muffle furnace under argon protection at 950° C. for 40 minutes, and quickly cool to 650° C. at 130° C. / h to obtain a multi-layer composite alloy block. The remaining steps are the same as in Example 2.
[0061] Comparative Example 6
[0062] The difference between Comparative Example 6 and Example 2 is that there is no step (1), and step (2) is changed to: 40 parts of nano-cerium carbide are placed in a smelting crucible, and 29 parts of nano-iron powder are melted to obtain a molten liquid, and the crucible is placed in a tightly coupled vacuum induction furnace. When the ambient temperature reaches 800°C, the atomizing medium is Ar gas, the atomizing pressure is 3.0 MPa, and the atomizing flow rate is 24m 3 / min atomizing and spraying the melt to obtain modified nanoparticles. The remaining steps are the same as those in Example 2.
[0063] Comparative Example 7
[0064] The difference between Comparative Example 7 and Example 2 is that step (1) is different, and step (1) is changed to: drying 10 parts of metal cerium powder to obtain nano-cerium carbide. The remaining steps are the same as those in Example 2.
[0065] Comparative Example 8
[0066] The difference between Comparative Example 8 and Example 2 is that there is no step (2). The remaining steps are the same as Example 2.
[0067] Effect example
[0068] Table 1 below shows the performance analysis results of the copper-aluminum alloy conductors for network base station radio frequency coaxial cables using Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.
[0069]
[0070]
[0071] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that by mixing Cu powder and modified nano-cerium carbide for one sintering, nano-cerium carbide fills the metal grain boundaries, allowing it to withstand more loads; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that using Cu-4Al powder and Cu powder as the intermediate layer for secondary sintering to form a strengthening phase can withstand greater loads and pressures and improve the strength of the alloy; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 3, it can be found that sintering three times with Al powder, Cu-4Al powder and modified nano-cerium carbide can improve the ductility of the alloy, inhibit the growth of grains in the alloy, and improve the toughness of the alloy; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 4, it can be found that the stacked layered structure formed by repeated three firings has closely bound elements and stacking faults. The transition interface with double gradient distribution can coordinate various deformation mechanisms, relieve stress concentration at the interface, and maintain good plasticity; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that slow cooling during annealing can form a continuous and smooth oxide film, which significantly improves the antioxidant performance; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the cerium element is diffused to the graphite surface at high temperature to form a cerium carbide layer, which can have an antioxidant effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 7, it can be found that the network structure of graphite can accelerate the electron transmission rate and enhance the conductivity; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 8, it can be found that iron powder is atomized and coated on the surface of cerium carbide to form a double-layer coated structure, which can be combined with the alloy during firing to enhance the conductivity of the alloy.
[0072] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A copper-aluminum alloy conductor for a radio frequency coaxial cable of a network base station, characterized in that: The aluminum alloy wire for the radio frequency coaxial cable of the network base station is prepared by multiple vacuum sintering of modified nano-cerium carbide and metal powder in a spark plasma sintering furnace, continuous annealing, rolling and wire drawing; the modified nano-cerium carbide is prepared from metal cerium, graphite and nano-iron powder; the metal powder includes Cu powder, Cu-4Al powder and Al powder; The copper-aluminum alloy conductor for the network base station radio frequency coaxial cable comprises the following preparation steps: (1) 6-14 parts of metallic cerium powder, 18-42 parts of graphite, 30-64 parts of NaCl and 3-7 parts of NaF were mixed uniformly, placed in a vacuum reactor for reaction for 30-70 minutes, then soaked in 71-93 parts of dilute acid solution for 1-3 hours, rinsed with 84-102 parts of water, and dried to obtain nano-cerium carbide; (2) 24 to 56 parts of nano-cerium carbide are placed in a smelting crucible, and 13 to 45 parts of nano-iron powder are melted to obtain a molten liquid, and the crucible is placed in a tightly coupled vacuum induction furnace. When the ambient temperature reaches 800° C., the molten liquid is atomized and sprayed to obtain modified nano-cerium carbide; (3) 42-56 parts of Cu and 13-27 parts of modified nano-cerium carbide are uniformly mixed and placed in a spark plasma vacuum sintering furnace, the temperature is raised to 800-1000°C at a certain rate, an external pressure of 25KN is applied, and the temperature is rapidly reduced by introducing argon gas, 19-25 parts of Cu-4Al powder and 3-31 parts of Cu powder are added, the temperature is raised to 800-1000°C at a certain rate, an external pressure of 25KN is applied, and the temperature is rapidly reduced by introducing argon gas, and then 21-33 parts of Al powder, 19-25 parts of Cu-4Al powder and 7-15 parts of modified nano-cerium carbide are added, the temperature is raised to 800-1000°C at a certain rate, an external pressure of 25KN is applied, and the temperature is rapidly reduced by introducing argon gas, and a composite alloy block is obtained; (4) repeating step (3) three times, placing the product in a muffle furnace under argon protection at 900-1000° C. for 30-50 min, and slowly cooling the product to 650° C. at a rate of 20-40° C. / h to obtain a multi-layer composite alloy block; (5) placing the multilayer composite alloy block in a horizontal continuous casting machine at a pouring temperature of 650 to 750° C. and a horizontal continuous casting speed of 800 to 1300 mm / min to obtain a round wire rod blank; (6) The round wire rod blank is placed in an alloy wire drawing machine at 450-550° C. and drawn into a wire with a diameter of 1.38 mm, thereby obtaining a copper-aluminum alloy wire for a radio frequency coaxial cable of a network base station.
2. The copper-aluminum alloy conductor for radio frequency coaxial cable of a network base station according to claim 1, characterized in that: The temperature of the vacuum reaction furnace in step (1) is 1100-1500° C., the vacuum degree is 0.01 Pa-0.1 Pa, and the dilute acid solution is 0.5-1.5 mol / L sulfuric acid solution.
3. The copper-aluminum alloy conductor for radio frequency coaxial cable of a network base station according to claim 1, characterized in that: The atomization spraying conditions in step (2) are: atomization medium Ar gas, atomization pressure 1.0-5.0 MPa, and atomization flow rate 18-30 m³ / min.
4. The copper-aluminum alloy conductor for radio frequency coaxial cable of a network base station according to claim 1, characterized in that: The particle sizes of the Cu powder, Cu-4Al powder and Al powder in step (3) are 250-450 meshes.
5. The copper-aluminum alloy conductor for radio frequency coaxial cable of a network base station according to claim 1, characterized in that: The vacuum degree of the spark plasma vacuum sintering furnace in step (3) is 1~15Pa.
6. The copper-aluminum alloy conductor for radio frequency coaxial cable of a network base station according to claim 1, characterized in that: The heating rate in step (3) is 80°C / min, and the rapid cooling rate is 100-160°C / h, cooling to 700°C.
Citation Information
Patent Citations
High-strength high-conductivity oxidation-resisting low-silver copper-base alloy and preparation thereof
CN101054654A
Copper wire used for semiconductor and preparation method thereof
CN106244844A